AN ANALYSIS OF EDUCATION POLICY IN THE PANDEMIC COVID-19 - Dedi Robandi (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The purpose of this study was to analyze education policy in Indonesia during the Covid-19 pandemic. This research is qualitative research with literature study techniques. Based on the results, the government issued a Circular Minister of Education and Culture No. 4 of 2020 concerning the prevention of Corona Virus Disease (COVID-19) in the Education Guide which aims to keep teaching and learning processes going on during the Covid-19 pandemic through Online or Distance Learning. Implementation of the Minister of Education and Culture Circular Letter Number 4 the Year 2020 still experiences various obstacles in terms of students including 1) not all students have online learning support facilities such as smartphones and laptops, 2) not all regions have internet networks, 3) limited internet quota. While from the teacher’s side, they have problems like this; 1) not all teachers can use technology in online learning, 2) the material delivered is not fully understood by students, 3) not all students can be present in online classes. Keywords: Learning, Covid-19, Minister of Education and Culture